UPAYA PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN PERANGKAT PEMBELAJARAN MELALUI SUPERVISI AKADEMIK YANG BERKELANJUTAN SDN 007 PANIPAHAN DARAT - Hamid, A. (JURNAL PAJAR (Pendidikan dan Pengajaran), 2017)
This research is based on observation in SD Negeri 007 Panipahan Darat got problem as follows: (1) low ofteacher competency in menyuun lesson plan especially syllabus and RPP; (2) the number of teachers preparingthe syllabus and lesson prior to teaching is still not maximal, only 60%; (3) in terms of quality, syllabus andgood RPP only reaches 30% of the syllabus and RPP made by the teacher; (4) difficulty of principals inevaluating teacher performance; (5) the difficulty of the principal evaluating the learning outcomes. This studyaims to increase the competence of teachers in preparing learning tools. In cycle 1 the number of teachers whocollect syllabus and RPP at the beginning of cycle 1, it can be seen that with the information of academicsupervision on the teacher can increase the quantity of teachers who make syllabus and RPP previously only62%, increased quantity to 74,25%. The results of the revised syllabus and RPP analysis show an increase in thequality of syllabus and RPP where the quality of A and B increased from 28 and 44 to 75 and 73%. From this itis also seen that the number of teachers who collect syllabus and RPP samples to 100%. Based on the result ofthis research, researcher can conclude that academic supervision continuously proven scientifically can improveteacher competence in arranging syllabus and RPP in SD Negeri 007 Panipahan Darat. This is evidenced by theincreasing number of good syllabus teachers from 28% to 75% after academic supervision. In addition, thenumber of good quality RPP also increased from 44% to 73%.